An evaluation of the severe acute respiratory infection surveillance system in Ireland - Louise Marron; Roisin Duffy; Joan O’Donnell; Lisa Domegan (BMC Public Health)
Abstract Background Expansion of the current single hospital site Severe Acute Respiratory Infection (SARI) surveillance programme in Ireland, to create a SARI sentinel hospital network, commenced in 2023. This evaluation aimed to assess the performance of key surveillance system attributes to improve and guide expansion. Methods A mixed quantitative and qualitative evaluation was conducted from September 2021 to November 2022 using European Centre for Disease Prevention and Control (ECDC) guidance as a framework. SARI surveillance data were analysed to assess completeness and timeliness. Semi-structured focus group discussions and key informant interviews and an online stakeholder questionnaire, evaluated usefulness, simplicity, flexibility and acceptability. Qualitative data were analysed using thematic analysis. Results Completeness of key variables including age and outcome was 100% (n = 747). COVID-19 vaccination status was completed in 89%, completeness of ethnicity data was only 0.6%. Median time from hospitalisation to commencement of data entry was one day (IQR 1–3). Time to receipt of whole genome sequencing (WGS) results was 40 days (IQR 30–61). Themes identified in the qualitative evaluation were the complexity of SARI surveillance, dependence on key individuals and skilled staff. Suggested areas for improvement included process automation and additional resources to improve timeliness and acceptability, particularly during epidemic or pandemic surge periods. Conclusions The SARI surveillance system reports complete and timely data. However, improvement in the timeliness of WGS data and recording of vaccination status and equity stratifiers e.g. ethnicity, would strengthen data quality. Priorities for expansion include process automation and adequate resource allocation, to enable reliable SARI surveillance at all times.